When x=0 y=50 when y=0 x=+\-5. -x^2 makes the parabola open downward y(x)=2x^2+50;y(3)=2*9+50=32
Answer:
Solving the equation
we get ![x=3+i \ , \ x=3-i](https://tex.z-dn.net/?f=x%3D3%2Bi%20%5C%20%2C%20%5C%20x%3D3-i)
Step-by-step explanation:
Noah's step to solve the equation
are:
![x^2 - 6x + 10 = 0\\x^2 - 6x = -10\\x^2 - 6x + 9 = -10 + 9\\(x-3)^2 = -1](https://tex.z-dn.net/?f=x%5E2%20-%206x%20%2B%2010%20%3D%200%5C%5Cx%5E2%20-%206x%20%3D%20-10%5C%5Cx%5E2%20-%206x%20%2B%209%20%3D%20-10%20%2B%209%5C%5C%28x-3%29%5E2%20%3D%20-1)
The next step is to take square root on both sides because: ![\sqrt{x^2}=x](https://tex.z-dn.net/?f=%5Csqrt%7Bx%5E2%7D%3Dx)
![\sqrt{(x-3)^2}=\sqrt{-1} \\x-3=\pm\sqrt{-1} \\x=\pm(\sqrt{-1})+3 \\](https://tex.z-dn.net/?f=%5Csqrt%7B%28x-3%29%5E2%7D%3D%5Csqrt%7B-1%7D%20%20%5C%5Cx-3%3D%5Cpm%5Csqrt%7B-1%7D%20%5C%5Cx%3D%5Cpm%28%5Csqrt%7B-1%7D%29%2B3%20%5C%5C)
Now, we know that: ![\sqrt{-1}=i](https://tex.z-dn.net/?f=%5Csqrt%7B-1%7D%3Di)
![x=\pm(i)+3\\x=3+i \ , \ x=3-i](https://tex.z-dn.net/?f=x%3D%5Cpm%28i%29%2B3%5C%5Cx%3D3%2Bi%20%5C%20%2C%20%5C%20x%3D3-i)
So, Solving the equation
we get ![x=3+i \ , \ x=3-i](https://tex.z-dn.net/?f=x%3D3%2Bi%20%5C%20%2C%20%5C%20x%3D3-i)
It's reflection; it's not translation
so answer is the last one.
d. No; it is one reflection after another with respect to the two parallel lines.
hope it helps
He is 40 mins away form home because he is going 65 mi/hr = 1 min per mile
hopefully that helps you make an equation